Ninth Five Year Plan 1997-2002 State of West Bengal Mid-Term Appraisal - Planning Commission (Planning Commission, 1997)
In West Bengal, we have attempted formulation and implementation of the Ninth Five Year Plan with a major social objective and a corresponding strategy for actions. The major objective has been one of increasing employment generation as far as possible through efficient enhancement of production in various spheres and, to support this thrust, an expansion in the infrastructure and social sectors. For achieving this objective, we have worked out a strategy for actions on the basis of an alternative approach to economic reforms. It is an alternative approach in the sense of upholding the interests of the common people, and also being formulated in our own terms, without any pressure of conditionalities of external loans. One of the essential pillars of this alternative approach is to ensure a move towards domestic equal competition, such as land reforms in agriculture and access to credit and other facilities for the common entrepreneurs in industry. The other pillar of the alternative approach to reforms is related to ensuring social action at appropriate levels in the spheres, such as infrastructure and social services, with effects benefiting larger sections of society. While ensuring this social action, the thrust has been on decentralisation - from the Centre to the States, from the State-level to the Panchayats and Municipalities in the districts and then further below, to the organised community action of local people, in coordination with the social objective mentioned earlier.
Mid-Term Appraisal
Government of West Bengal